Detection of Prunus Necrotic Ringspot Virus (PNRSV) and Apple Mosaic Virus (ApMV) in Rose (Rosa spp.) Plants in Konya Province - Adile Tuğçe Orhan; Serkan Yeşil (Turkish Journal of Agriculture: Food Science and Technology)
This research was conducted to determine the presence of Prunus necrotic ringspot virus (PNRSV) and Apple mosaic virus (ApMV) that can cause infection in rose (Rosa spp.) plants grown in Konya province. For this purpose, field and laboratory studies were carried out in areas where roses are mostly grown for landscaping purposes, and infection rates were calculated with the data obtained. The hypothesis of the study is that roses in Konya province may be infected with PNRSV and ApMV and the presence of these viruses can be determined. In line with this hypothesis, various rose growing areas in Konya province were selected as the research area. During the field studies in 2023, guided sampling was carried out and 94 leaf, branch and flower samples were collected from different rose varieties. The collected samples were tested for determining of PNRSV and ApMV infections by Double Antibody Sandwich (DAS) ELISA method, which is one of the serological testing methods in the laboratory. As a result of the tests, it was revealed that the single infections of PNRSV and ApMV were present in 12 and 11 samples of rose plants in Konya province. The total infection rate of both viruses in the province was calculated as 24.47%. Also, PNRSV+ApMV mixed infections were detected in 2 samples. In this study, the infections of PNRSV and ApMV on roses in Konya province were determined for the first time by serological methods. These results will serve as an important source of information for rose producers and agricultural engineers in the region and will allow the development of strategies to control the spread of viruses and minimize infections.